Restorative Justice Policy as Criminal Settlement in The Law of Information and Electronic Transaction (ITE) - Sasmita, Ajeng Risnawati (UIN Sunan Kalijaga Yogyakarta, 2021)
Restorative justice in conflict resolution is an effort to resolve between criminals and victims of crime in criminal cases directly. More specifically, restorative justice seeks a way out by considering the good for all parties, be it for the perpetrator, the victim, or the victim's family. This article defines the basic concept of applying the Restorative Justice Policy as the settlement of criminal cases in the Electronic Information and Transaction Law. This article is a qualitative research using a conceptual normative approach. Data were collected through literature study, then analyzed using a data reduction process, data presentation and conclusion drawing. The application of Restorative Justice as a settlement of criminal cases as regulated in the legislation concerning Electronic Information and Transactions (UU ITE) is deemed appropriate considering that in the settlement of criminal cases, investigators must have the principle of prioritizing restorative justice in case settlement, and criminal law is the last resort that can be used. carried out as an effort to enforce the law (ultimum remidium), as stated in the Circular Letter Number: SE/2/11/2021 and the Chief of Police's Telegram Letter No. ST/339/II/RES.1.1.1./2021. With the process of returning to its original state (peace between the two parties), then criminal cases can be resolved and there is no need to continue the process in the judicial process.